2014
DOI: 10.1021/ez500229b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Incorporation of Abiotic S and N into Prairie Wetland Dissolved Organic Matter

Abstract: Materials and MethodsSurface water samples were collected in pre-combusted (450 °C, 6 hr) glass jars, filtered through pre-combusted (550 °C, 5.5 hr) glass fiber filters (0.7 m, Millipore) on site, and stored on ice for transport. Upon arrival in the laboratory, the samples were 0.22 m filtered (mixed cellulose esters, Millipore) and stored at 4 °C. The porewaters were collected by centrifugation 1 and were then 0.2 m filtered (PTFE, Pall Life Sciences). Sulfate and other anions were measured via ion chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 36 publications
6
71
0
Order By: Relevance
“…Another unique feature of the Lake Vida brine DOM is that the assigned The N and S containing formulas were distributed broadly within the van Krevelen space that was occupied by the Lake Vida DOM fractions. In terrestrial, prairie wetland systems, this broad distribution has been interpreted as evidence for the abiotic incorporation of N and S (Sleighter et al, 2014). However, other studies have demonstrated that microbial processing can result in the production of a diversity of N and S containing formulas (Lechtenfeld et al, 2015).Thus, the fact that the N and S containing formulas occupy the same van Krevelen space as the DOM fractions does not preclude the abiotic or biotic incorporation of N and S into the Lake Vida DOM.…”
Section: Preservation Of the Microbial Signature Of The Dom During Enmentioning
confidence: 99%
“…Another unique feature of the Lake Vida brine DOM is that the assigned The N and S containing formulas were distributed broadly within the van Krevelen space that was occupied by the Lake Vida DOM fractions. In terrestrial, prairie wetland systems, this broad distribution has been interpreted as evidence for the abiotic incorporation of N and S (Sleighter et al, 2014). However, other studies have demonstrated that microbial processing can result in the production of a diversity of N and S containing formulas (Lechtenfeld et al, 2015).Thus, the fact that the N and S containing formulas occupy the same van Krevelen space as the DOM fractions does not preclude the abiotic or biotic incorporation of N and S into the Lake Vida DOM.…”
Section: Preservation Of the Microbial Signature Of The Dom During Enmentioning
confidence: 99%
“…Aromatic terrestrial DOM compounds generally decrease along salinity gradients while the DOM heteroatom content increases due to autochthonous production (Sleighter and Hatcher, 2008;Osterholz et al, 2016). Likewise, the alteration of DOM under different redox-regimes can leave identifiable molecular imprints such as the relative enrichment of sulfurcontaining compounds (Schmidt et al, 2009;Seidel et al, 2014Seidel et al, , 2015aSleighter et al, 2014;Gomez-Saez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of sulfur likely protects labile organic matter from microbial alterations (Anderson and Pratt, 1995). There are also indications that natural DOM may be sulfurized in sulfidic marine systems because DOS concentrations are distinctly higher in sulfidic environments than in oxic ones (Sleighter et al, 2014;Gomez-Saez et al, 2016). Benthic fluxes from anoxic marine sediments, where carbon oxidation rates are high, contribute major amounts of iron (Dale et al, 2015) and DOM (Burdige and Komada, 2014) to the ocean.…”
Section: Introductionmentioning
confidence: 99%